Factors affecting the performance of library and information professionals in the Librarians' Licensure Examination (LLE) 2006-2010, part 1 age, gender, and type of examinees - Ramos, Mila M.; Ananoria, Arabella M.; Nera, Corazon M. (2012)
Presents factors such as age, gender and type of examinees, that affect the performance of the LLE takers for the years 2006-2010. These factors were then correlated with the passing percentage for the years 2005-2010. Found out that all these factors do not significantly affect performance in LLE.